Pengaruh Desain Interior terhadap Produktivitas Kerja Pustakawan di Perpustakaan Perguruan Tinggi Negeri Surabaya - Amira Oribia Wanda Sasmita (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
Labor productivity is a major thing that generated real by employees under the auspices of an organization, is no exception librarian. Librarians work productivity is generally influenced by various factors. One of the factors that can affect work productivity is the environment in which they work. This study aimed to determine the influence of interior design workspace to work productivity librarian at the Library of the State University of Surabaya. This study uses a quantitative approach explanative survey method. Sampling using a sampling saturated with the total number of 77 respondents who are librarians who work Surabaya State University Library consisting of Airlangga University Library, Surabaya State Library Institute of Technology, Surabaya State University Library, and Electronic Engineering Polytechnic Institute of Surabaya. Multiple linear regression was used to determine the effect of five variables interior design. Based on the results of partial test is known that there is no significant influence of furnishings, noise, and lighting on work productivity. Variable temperature and the layout has a significant impact on labor productivity. Based on the results of the F test is known that a significant difference between interior design factors (X) on the productivity of librarians (Y). Interior design factors have 54% influence on the productivity of the librarians at the Library of the State University of Surabaya, while 46% are influenced by other factors outside the interior design factors.